Representation of Social Inequality in the Netflix Series Arcane (Semiotic Analysis of Roland Barthes Model) - Perdhana, Pramudya Dexsa; Kusuma, Arif Surya (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This research aims to identify how meaning is related to social inequality in the Netflix series Arcane. Methodology: The method used in this research is qualitative content analysis using Roland Barthes' semiotic theory analysis. The sampling technique in this research used a purposive sampling technique. The data collection method in this research is documentation. The data validity technique used is the data triangulation technique. Results: The research results show that there are two categories that appear in the Netflix series Arcane. First, the representation of social inequalities that emerge includes educational inequality, ethical inequality, housing inequality, and economic inequality. Second, marginalization as a form of symbolic violence. This research seeks to identify how meaning is related to social inequality in the Netflix series Arcane. Applications/Originality/Value: The differences in this research include the research object, literature, and theory used, as well as research results.